Langzeitpflegeeinrichtungen in der COVID-19-Pandemie: Überlegungen auf dem Weg zurück in die Normalität - Gosch, M.; Altrichter, D.; Pfluegner, M.; Frohnhofen, H.; Steinmann, J.; Schmude-Basic; Adamek, A.; Johnscher; Kandler, U.; Wunner, C.; Waller, C.; Speer, R.; et al. (Zeitschrift für Gerontologie und Geriatrie, 2021)
Long-term care facilities (LTCF) were and are particularly affected by the COVID-19 pandemic. The dimensions of the outbreaks and the high mortality among residents led to massive restrictions in LTCFs, especially in the area of social contacts and activities but also in areas of medical care. With the start of vaccinations and the improved testing options, the situation has now changed and existing restrictions must be evaluated to determine whether they are still appropriate. In an interprofessional and interdisciplinary group of experts, considerations have been formulated on how a way back to normality could look like in LTCFs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Corona; Rehabilitation; Social contacts; Vaccination; Visits